EFFECTIVENESS OF COUNSELING USING LINE AS SOCIAL MEDIA APPLICATION ON THE KNOWLEDGE OF DENTAL AND ORAL HEALTH MAINTENANCE - Amalda Ayu Utami Hasibuan; R. Harry Dharmawan Setyawardhana; Ika Kusuma Wardani (FKG Unlam, 2023)
ABSTRACTBackground: Oral health is an integral component of public health. The incidence of oral disease is mostly due to neglected oral hygiene factors, especially in adolescents who begin to develop more independence and self-care responsibilities including oral and dental hygiene that are effectively manage by themselves instead of their parents. Therefore, this period requires proper direction for adolescents as a form of prevention in maintaining oral health. However, during the Covid 19 pandemic, direct outreach activities were avoided so that Line as social media application was used to overcome obstacles in delivering counseling materials. Purpose: To analyze the effectiveness of outreach using Line as social media application for students at SMP Negeri 1 Rantau, Tapin Regency.Methods: Using true experimental design with pretest-postest design with control design with simple random sampling technique. The research was conducted at SMP Negeri 1 Rantau Tapin Regency with a sample of 114 respondents.Results: The Wilcoxon test in the poster intervention group obtained a significance value of 0.003 <0.05 and the poster intervention 0.015 <0.05,Referring that there was a difference in knowledge between before and after counseling. While the control group obtained a significance value of 0.619> 0.05, referring that there was no difference in knowledge between before and after counseling was given. Conclusion: counseling using Line as social media application is effective in increasing knowledge of oral health maintenance. Keywords: adolescent, counseling, oral health, social media